Wilms' tumor in low- and middle-income countries: survey of current practices, challenges, and priorities - Megan Thuy Vu; Jaime Shalkow; Bindi Naik-Mathuria; Sajid S. Qureshi; Doruk Ozgediz; Kokila Lakhoo; Hafeez Abdelhafeez; On behalf of the Pan African Paediatric Surgery Association (PAPSA) (SpringerOpen, 2022)
Abstract Purpose To identify the current practices and priorities in Wilms' tumor management for surgeons in low- and middle-income countries (LMICs). Methods One hundred thirty-seven pediatric surgeons from 44 countries completed surveys on Wilms' tumor surgical strategy in LMIC. This survey was distributed through the Global Initiative for Children's Surgery, Pan-African Pediatric Surgical Association, and Latin American Pediatric Surgical Oncology Group. Results Ninety-two respondents (67.2%) participated from 19 lower middle-income countries (43.2%). Twenty-one respondents (15.3%) participated from nine lower income countries (20.5%). Nineteen respondents (13.9%) participated from 13 upper middle-income countries (29.5%). Most providers do not obtain biopsy for suspected Wilms' tumor (79%). Delayed resection after preoperative chemotherapy is the preferred approach (70%), which providers chose due to protocol (45%), to decrease tumor rupture (22%), and to decrease complications (8%). The providers' goal was to prevent tumor spillage and upstaging (46%) or to prevent bleeding, complication, or other organ resections (21%). Most surgeons believed that upfront resection increased the risk of tumor spillage (72%). Conclusion Providers in LMICs prefer delayed resection after preoperative chemotherapy to reduce the incidence of tumor spillage and upstaging of Wilms' tumor. An evidence-based guideline tailored to the LMIC context can be developed from these findings.